Impacts of Climate Change and Air Pollution on the Tourism Industry: Evidence from Southeast Asia - NGUYEN, Thi Gam (Journal of Environmental Management and Tourism, 2020)
This paper examines the effects of climate change (greenhouse gas emissions) and air pollution (methane and nitrous oxide emissions) on the tourism industry in Southeast Asian (SEA) countries, using dynamic panel data for the period 1998-2012. A two-stage least squares (2SLS) method is applied by adding an instrumental variable and lagged variables to solve for endogeneity. 2SLS estimation shows that air pollution has a negative effect on total tourist arrivals but there was not enough evidence to reach a conclusion about the impact of climate change. Surprisingly, nitrous oxide emission was the key driver which negatively and significantly affected tourist demand. This emission is largely caused by high levels of fossil fuel consumption and motor vehicle traffic. These findings suggest that governments may need to make critical policy decisions about whether to give up short-term economic growth to pursue long-term environmental improvement, with a view to enhancing the quality of tourist destinations in Southeast Asia in the future.